HOTS-Based Instrument Development Training in the Independent Learning Curriculum for Enonekmese State Middle School Teachers - Tandjung, Ferofianes Linda; Banik, Lodia Amelia; Ningati, Dwi Kristin; Foeh, Yonatan; Selan, Anita (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2025)
The Independent Curriculum emphasizes the importance of authentic assessment to measure students' learning achievement. One form of authentic assessment that can be used to measure HOTS abilities is a HOTS-based instrument. Teachers at Enonekmese State Middle School have so far had difficulty in compiling HOTS-based instruments. This training is expected to increase teachers' insight into the rules and how to compile HOTS-based assessment instruments. There are three stages carried out in this training activity, namely: 1. Planning. At this stage, the activity implementer contacts the training presenter, determines the location of the activity and prepares all activity needs. 2. Implementation. At this stage, the training activity is carried out for one day by presenting 2 speakers. 3. Evaluation. After the activity is completed, an evaluation is then held to see the achievement of the activities that have been carried out. This PkM activity was carried out in two sessions with different forms. Participants were given an understanding of the independent learning curriculum and received training and assistance in preparing HOTS-based evaluation instruments. This training provides a significant contribution to teachers in gaining a number of knowledge and competencies related to the independent learning curriculum and the preparation of HOTS-based evaluation instruments.